Material Development Based on Digital Storytelling Activities and Assessment of Students’ Views - Ozlem Ayvaz Tunc (Institute of Advanced Engineering and Science, 2017)
This study was designed as a case study. The study was conducted in Anatolian Fine Arts High School during the spring semester of 2014-2015 academic year. The sample of the study consisted of a total of 10 students from 9th and 10th grades who voluntarily participated in the study. Semi-structured interviews were conducted with the 10 students named at the end of every activity. Assure instructional design model was used while designing digital storytelling activities. The data obtained from the study were analyzed through thematic analysis based on qualitative research method. Reliability method suggested by Miles and Huberman was used for reliability assessment of the study. The reliability of the thematic coding of the results was found to be 0,95 as a result of assessments. Based on the findings that digital storytelling has multidisciplinary interaction competence, it is thought that it will be appropriate to conduct future studies in different schools and fields.